THE MULTIPLE ROLES OF EXHIBIT LEARNING IMPACT ASSESSMENTS IN A SCIENCE CENTRE - Monteiro, Paulo Henrique Nico; Barriault, Chantal; Bizzo, Nelio (Educere et Educare, 2018)
Visitor’s engagement with an exhibit could be considered as an important learning indicator and predictor. Based on this idea, Barriault and Pearson (2010) proposed an assessment framework, which has been constantly used by a Canadian Science Centre - Science North for different areas and proposes since 2005. This paper presents and analyses this experience as well as discuss some features of this framework as accuracy, feasibility and adaptability for other contexts. Documental analysis and interviews with Science North science staff and directors were held in order to deeply understand how this assessment method has been used at this Science Centre over these 10 years. All interviewees pointed that data collected through this method has been used to make changes in an exhibit in order to improve visitor's engagement, in floor-staff training programmes, as an important information for international partnerships and sales and, more recently, as a Centre's management indicators. In addition, all respondents stressed the accuracy and feasibility as strengths of the tool as far as data collected is easy to understand and "make sense" for all staff. Science North's experience shows that collecting and analysing learning data can play an important role in providing useful findings for different areas of a science centre, and could be an important way to improve visitor’s experience at the museum.